Treatment phasespecific frequency and conditions for developing ТТV and HGV infection in children with new onset acute lymphoblastic leukemia - L. Yu. Poslova (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Currently, it is believed that TTV and HGV display multifaceted activities in developing diverse acute and chronic processes (disorders affecting the liver, respiratory tract, hematopoiesis oncology diseases etc.). Transfusion of contaminated blood and its components contribute in transmission of HGV and TTV infections. In connection with this, examining a role for HGV and TTV in etiological structure of pediatric liver damage in acute lymphoblastic leukemia (ALL) as well as their relation to developing toxic liver damage against during ongoing therapy is of special interest. Our study was aimed at assessing hospital-acquired HGV and TTV infection and its potential effect on the incidence rate and liver damage intensity in children with acute lymphoblastic leukemia. A rationale for the current study was previously verified hepatitis of unknown etiology excluding viral hepatitis B and C in such patients. In the study, there were examined 99 patients stayed at the Department of Hematology as well as 286 samples from diverse donor bloodderived products. The data obtained were examined by using epidemiological methods (retrospective and near real-time epidemiological analysis, prospective observation), microbiological monitoring, ELISA, PCR followed by analyzing with variation statistics methods. It was found that 51 children, mainly aged 2–4 years (47.1%), were diagnosed with new onset acute lymphoblastic leukemia during a six-year follow-up study. Treatment phase-specific dynamic investigation demonstrated a progressive increase in frequency of HGV-infected ALL patients from 9.8% (day 15 of therapy) up to 45.1% (maintenance therapy). Moreover, a therapeutic intervention was associated with TTV infection detected in 100% cases in baseline TTV DNA-negative patients 100%, and its rate was significantly increased. Thus, our study allowed to demonstrate that 48% and 77% ALL pediatric patients were infected HGV and TTV, respectively, at initial treatment phase (remission induction), that was paralleled with administering the maximum-dose parenteral therapy, including transfusion therapy. Finally, assessing blood donor-derived preparations allowed to detect HGV RNA and TTV DNA in 6.6±1.46% and 19.3±2.9% cases, respectively.